Fiscal Disaster Risk Assessment Options for Consideration : Pakistan - World Bank Group; Global Facility for Disaster Reduction and Recovery (World Bank, Washington, DC, 2015)
Pakistan is vulnerable to a number of adverse natural events and has experienced a wide range of disasters over the past 40 years, including floods, earthquakes, droughts, cyclones, and tsunamis. The World Bank is supporting the Government of Pakistan (GoP) in building capacity in the area of disaster risk management (DRM) in order to build resilience from both humanitarian and fiscal shocks associated with natural disasters. The World Bank is providing technical assistance to the GoP for the development of a national disaster risk financing strategy. This non-lending technical assistance aims to: (i) assess the fiscal exposure of the GoP to natural disasters; (ii) present options for the development of a national strategy to improve financial response capacity for natural disasters; and (iii) promote property catastrophe risk insurance for both public and private dwellings. Disaster risk financing and insurance (DRFI) is one of the five pillars in the proactive and strategic framework for DRM promoted by the World Bank. The World Bank has been promoting a proactive and strategic framework for DRM based on five pillars: (i) risk identification; (ii) risk reduction; (iii) preparedness; (iv) financial protection; and (v) resilient recovery. Chapter one is introduction. Chapter two presents an overview of the budget processes for the financing of natural disaster losses during each of the three post-disaster phases. Chapter three provides a preliminary financial disaster risk assessment for Pakistan, focusing particularly on the fiscal impact of natural disasters. Chapter four presents an overview of the private catastrophe insurance market; and chapter five reviews the options for future financing of natural disaster recovery and reconstruction expenditures.